Composition of Soil Arthropods in the Urban Forest Area of Arboretum Cibubur, East Jakarta - Ruslan, Hasni; Tobing, Imran SL; Pratama, Cristian Flo (Journal of Tropical Biodiversity, 2025)
The Cibubur Urban Forest, designated by the DKI Jakarta Regional Government as a conservation area, serves as a vital ecological patch supporting diverse plant vegetation and associated organisms. This study investigates the composition and diversity of soil arthropods within the forest, focusing on their ecological roles across different habitat types. Field research was conducted in March 2024 using pitfall traps (15 traps per habitat, filled with 70% alcohol) deployed for three days. Specimens were collected from four distinct habitats and classified taxonomically. Results identified six arthropod classes: Arachnida, Chilopoda, Collembola, Crustacea, Diplopoda, and Insecta, with Insecta being the most dominant. A total of 16 orders were recorded, with Collembola, Coleoptera, and Diptera exhibiting the highest abundance, while Mantodea and Isoptera were the least represented. Habitat 1 showed the highest arthropod diversity, whereas Plot 2 had the lowest. Ecological analysis revealed arthropod functions as predators, decomposers, scavengers, herbivores, and carnivores, underscoring their critical roles in maintaining forest ecosystem stability. These findings highlight the Cibubur Urban Forest’s significance as a biodiversity hotspot and emphasize the need for habitat-specific conservation strategies to preserve soil arthropod communities and their ecological services.